Hubungan antara Pemberian Radioterapi dengan terjadinya Distress, Anxiety, dan Depresi pada Penderita Kanker Payudara - Yohana Prima Ceria Anindita, Carla Raymondalexas Marchira, Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2010)
Background: As the world rates of breast cancer have increased, there has been a growing awareness of psychological effect of diagnosis and treatment and its role in the outcome of chronic disorders. Radiotherapy for breast cancer is an intense and cyclic treatment associated wi th number of side-ef fects. The sociodemographic factors of age, gender, marital status, education, immigrant status, income and insurance have consistently been identified as important factors in explaining the variability in distress, anxiety, depression prevalence rates.Objective: To evaluate the effect of radiotherapy on distress, anxiety and depression among breast cancer patients based on sociodemographic factors.Methods: Screening tools for measuring distress of National Comprehensive Cancer Network and Hospital Anxiety and Depression Scale (HADS) was used to evaluate breast cancer patients. A descriptive study using a cross sectional design performed in Radiotherapy Division of RSUP Dr. Sardjito and breast cancer patients were asked to complete the DIC and HADS after radiotherapy. Participants were 30 patients in RSUP Dr. Sardjito.Result: Education level was the only factor found significantly to influence depression status, depression status were different based on education level (p=0.019), high education level had less depression status. A significant, moderate correlation was obtained between distress and depression scores ( r = 0.561**, p =0.001).Conclusions:  There is a difference on depression status based on education level in breast cancer patients who got radiotherapy. A significant, moderate correlation was obtained between distress and depression scores.Keywords: distress, anxiety, depression, breast cancer patients, radiotherapy, screening tools for measuring distress of National Comprehensive Cancer Network, the HADS questionnaires, sociodemographic factors.